Estimating wave attenuation at the coastal land margin with a GIS toolbox. (October 2020) - Foster-Martinez, Madeline R.; Alizad, Karim; Hagen, Scott C.
Abstract: Wave attenuation is a key process that impacts activities at the coastal land margin and is an ecosystem service provided by many natural landscapes. Traditional modeling tools for wind wave attenuation require advanced expertise to apply. We present an alternative, GIS-based option for estimating wave attenuation, the Wave Attenuation Toolbox (WATTE). The outputs are a map of wave height transmission as a percentage of the original wave height and a line demarking the extent of wave exposure onshore. WATTE supports a variety of inputs, ranging from outputs of ecological and landscape evolution models to remote sensing data, and past, present, and future conditions can be analyzed. The present version of WATTE models wave attenuation as an exponential decay process, and a recommendation table for exponential decay constants is derived from previous studies. Three examples of applying WATTE to marsh environments are described. Highlights: A GIS-toolbox is described that adds information on wave attenuation to existing datasets. The toolbox input is flexible allowing for application to data-limited locations. Wave attenuation through marsh vegetation is modeled as an exponential decay process in three given examples.